Screening statues : sculpture and cinema - Jacobs, Steven (Film producer); Felleman, Susan; Adriaensens, Vito; Colpaert, Lisa (Edinburgh studies in film and intermediality., 2017)
This is the first book to focus on the relationship between sculpture and the silver screen. It covers a broad range of magical, mystical and phenomenological interactions between the two media, from early film's eroticized tableaux vivants to enigmatic sculptures in modernist cinema. Sculptures are literally brought to life on the silver screen, while living people are turned into, or trapped inside, statuary. The book examines key sculptural motifs and cinematic sculpture in film history through a series of case studies and through an extensive reference gallery of 150 different films. Considering the work of directors like Georges Melies, Jean Cocteau and Alain Resnais, as well as films like House of Wax, Jason and the Argonauts and Clash of the Titans, this is an innovative exploration of two different media, their artistic traditions and their respective theoretical paradigms.